Phytochemical investigation and effective therapeutic potential of plants extracts against breast and ovarian cancer cell lines: compounds from zizyphus mauritiana and triticum aestivum - Tabassam, Qudsia; Ahmed, Sibtain; Mehmood, Tahir; Iqbal, Mudassir; Saeed, Shagufta; Ahmad, Muhammad Mushtaq; Sultan, Ayesha; Rehman, Muhammad Misbah ur; Qadir, Rahman; Ullah, Azmat; Abdul Rehman, Natasha (Cellular and Molecular Biology, 2021)
ancer is the leading cause of death, accounting for approximately one out of six people dying with this disease worldwide. Among all, the breast and ovarian cancers are top-ranked causes of women mortalities compared to other disorders. Although, there is advancement in technologies, but still, there are unresolved concerns to overcome the global disease burden. Currently, plants are being explored as a natural remedy to cure disorders. This research was planned to explore phytochemicals in methanolic extracts of Zizyphus mauritiana and Triticum aestivum, and their pharmacological activities were studied through Agrobacterium tumefaciens bacteria, in vitro breast cancer cell line and ovarian cancer cell line to find out novel candidates in disease control and prevention. Eleven different types of bioactive compounds were analysed in the tested extracts. The highest crude extracts percentage (75±0.02) was observed with Z. mauritiana. The extracts showed promising cell growth inhibition and tumor initiation inhibition in potato disc assay. MTT assay and Incucytes imaging analysis revealed that Z. mauritiana extract had a higher anticancer potential with 40 ± 0.92 cell viability against breast cancer cells (SKBR3) and 45 ±0.29 against ovarian cancer cells (SKOV3). In conclusion, these extracts could be used as chemotherapeutics owing to their cheapness, and easy availability. While detailed study is required for further purification and characterization of bioactives/target compounds and in-vivo activity confirmations.